The emerging role of iron acquisition in biofilm-associated infections - Oliveira, Fernando E. (2021)
A possible association between iron and biofilm formation has been explored for a long time. Here, we focus on major recent advances that shed light on the mechanisms behind this relationship and discuss how siderophore-mediated iron acquisition may impact the virulence of important nosocomial pathogens.